INOVASI PEMBELAJARAN BERBASIS KASUS MANAJEMEN LINGKUNGAN - Fenty Fauziah; Fitriansyah; Bambang Sutedjo; Muhammad Said (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Case-Based Learning (CBL) emphasizes effective problem-solving, discussion of specific situations, and real-life examples within a business context. This study focused on cases related to environmental preservation and its impact on business from economic, social, political, and legal perspectives. The research was conducted at Sungai Karang Mumus School (SKM School), Muang Ilir Street, Betapus, Samarinda. The study aimed to analyze the effect of CBL on students’ learning motivation and outcomes. The research used a pre-post-test design with a population of 25 postgraduate Management students at Universitas Muhammadiyah East Kalimantan, employing total sampling. Data analysis used non-parametric statistics with a Paired Sample t-test and the Wilcoxon test. The results indicated a significant improvement in students’ motivation and learning outcomes after implementing the CBL method. Motivated students achieved better learning outcomes, demonstrated critical thinking skills, and applied prior knowledge effectively in problem-solving. This study encourages educators and institutions to adopt CBL as an innovative learning approach.